RECLAIMING BANYUMAS IDENTITY AN INTERPRETIVE STUDYABOUT IDENTITY AND CHARACTER OF LOCAL SOCIETY BASED ON LITERARY STUDIES OF HISTORY, ATTITUDES, BEHAVIOR, ARTS AND CULTURE - Oki Edi Purwoko (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2016)
The objectives of these study is to explore more about Banyumas cultural identity through. Caused by politics and power in the past, some of writings indicated that there were alienation, seclusion towards Banyumas culture due to political objectives created by Keraton elite and Colonial ruler in the past. As many Javanese culture, This view exclude other forms of arts and culture which flourished besides the mainstream culture or in this case high culture as Keraton had. And then labeled those art as folk art, sometimes not representation of Javanese culture or even as included as non art at all. For instance, Prior to Indonesian Independence in 1945, art, culture and symbols represented by keraton in Yogyakarta and Surakarta considered appraised a higher status compared to Banyumas culture and identity. Contradicted with inferior behavior in general, Banyumas attitudes towards Keraton, are resistant, doubt, lowered, and even mocked them. It showed in daily life interactions especially when they dealt with Bandek language, the sublimity in Keraton rituals, art culture and philosophy and also nobility symbols. Banyumas people are commonly proud of their culture and identity but at the same time they feel inferior towards Keraton or Javanese mainstream culture. This study concentrated in inferiority complex phase based on Adlerâ€™s thesis. Response coming from Banyumas people is often paradoxical with the inferiority as a general. One of its implications was the emergence of new character as compensation. These compensation commonly reflected in two ways, first would be elevate ownâ€™s status and secondly lowering the others.The common attitudes shown on this compensations for example passionally willingness to be superior, insulting,hostile and indifference.Â Tujuan utama dari penelitian ini adalah untuk melakukan telaah lebih dalam mengenai kebudayaan Banyumas. Karena adanya politik dan kekuasaan yang bermain di masa lalu, beberapa tulisan mengindikasikan adanya alienasi, pengasingan terhadap kebudayaan Banyumas yang disebabkan karena tujuan politis yang diciptakan pihak â€“ pihak keraton dan penguasa kolonial. Seperti kebudayaan Jawa yang lain, bentuk kesenian dan kebudayaan yang berkembang selain kebudayaan Keraton Jawa tidak dianggap sebagai perwakilan bentuk kebudayaan Jawa. Setelah itu, ada pemberian cap sebagai kebudayaan rakyat, kebudayaan yang rendah atau bahkan bukan kebudayaan sama sekali. Sebagai contoh, sebelum Kemerdekaan di tahun 1945, seni, budaya dan simbol - symbol yang dikeluarkan keraton Jogjakarta dan Surakarta dianggap memiliki status yang lebih tinggi dibanding identitas dan Kebudayaan yang ada di Banyumas. Berlawanan dengan sikap inferior secara umum, sikap orang Banyumas terhadap Keraton bersifat melawan atau menentang, ragu, merendahkan dan bahkan mengejek. Hal ini terlihat dalam interaksi setiap harinya terutama terkait dengan Bahasa Bandek yang khas digunakan pihak Keraton, Keagungan ritual di dalam keraton, seni budaya, filosofi serta simbol simbol keningratan. Orang Banyumas secara umum merasa bangga atas identitas kebudayaan yang dimilikinya namun di saat yang sama merasa inferior jika dibandingkan dengan kebudayaan Keraton yang dianggap sebagai kebudayaan Jawa yang dikenal secara umum. karena alienasi tersebut, kebudayaan Banyumas menurut Anderson Sutton, mengalami perendahan secara politis dan artistik terhadap Kebudayaan Keraton â€œâ€subordinate politically and inferior artistically to the greatcourtsâ€(Sutton, 1986 : 116). Penelitian ini terfokus terhadap inferiority complex yang diambil dari pemikiran Alfred Adler. Karena respons dari masyarakat Banyumas yang seringkali berlawanan dengan sikap inferior secara umum. Salah satu implikasi dari sikap ini adalah compensation atau kemunculan sikap lain (Broh, 1979 : 178). Sikap ataun kompensasi ini umumnya muncul dalam dua sikap, yang pertama adalah dengan menaikkan status yang dimilikinya dan yang kedua merendahkan status yang dimiliki pihak lainnya. Sikap yang umum tercermin dari kompensasi tersebut adalah keinginan yang menggebu untuk unggul, memusuhi, merendahkan, melawan tidak peduli.